Analysis of Performance Characteristics Predicted From Several Experimental Data and Conversion Methods for Pumps as Turbine Application Using Statistical Techniques - Mdee, Ombeni J.; Kimambo, Cuthbert Z. M.; Nielsen, Torbjorn K.; Kihedu, Joseph (Tanzania Journal of Engineering and Technology, 2021)
Different performance characteristics have been indicated when running centrifugal pumps in the reverse direction. The water flows from the discharge side of the pump to the suction side to run in the reverse direction and generate the mechanical rotational energy for the micro-hydropower plant. The current study evaluates the extent of variation of performance characteristics predicted by several experimental data from different pump-specific speeds and conversion methods. The performance characteristics discussed include the head, flow rate, efficiency and specific speed. The flow rate and head of a pump operating in pump mode divided with the characteristic of the pump operating in the reverse mode, at the best efficiency point, the resulting coefficient of determination (R 2 ) values were of 0.890 and 0.708, respectively. Also, the graph of head versus flow rate coefficients, which is a second- order polynomial function, has shown the value of R 2 of 0.954 for pump-specific speed ranging between 9 and 94 rpm. However, the pump in the reverse mode has smaller performance characteristics for efficiency and specific speed compared to the pump mode operation with R 2 of 0.966 and 0.999, respectively. Furthermore, schematic empirical statistical models were developed to predict the performance characteristics of several conversion methods using pump data obtained from the manufacturers. Keywords: Conversion method, pump as turbine, performance characteristics, statistical techniques.